REFLEKSI PRAKTIK LAPANGAN DALAM PROGRAM PPL DI UNU YOGYAKARTA OLEH MAHASISWA MAGISTER MANAJEMEN PENDIDIKAN ISLAM UIN SUNAN KALIJAGA - Muthia Rabiah, Vira (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study explores the implementation of Field Practice (PPL) by Master's students in Islamic Education Management at UIN Sunan Kalijaga during their professional placement at Nahdlatul Ulama University (UNU) Yogyakarta. The research examines the process of integrating educational management theories with institutional practices, focusing on opportunities for enhancing organizational development. Through qualitative inquiry, the study highlights the importance of collaborative approaches in implementing transformational leadership and participatory planning models. Findings reveal valuable insights into optimizing institutional processes, fostering technological adoption, and building consensus for educational innovation. The study offers constructive recommendations for aligning academic preparation with professional practice in Islamic higher education management.